THE USE OF STORY GRAMMAR IN TEACHING READING NARRATIVE TEXT - Sartika, Ika (2014)
This study is concerned with the implementation of story grammar as proposed by Florida Center for Reading Research (2007) and Gardill &Jitendra (1999).The participants of the study were 30 ninth grade students of one junior high school in kuningan. It aims to answer the following research questions: 1) How can story grammar develop students' reading comprehension of narrative text? 2) What are the students' responses towards the use of story grammar in improving their reading comprehension of narrative text? This study employed a qualitative case study research method. The data were gathered from three resources: a) classroom observation in which the researcher acted teacher in implementing story grammar. These data gained to provide information about the process of implementing story grammar in teaching reading comprehension of narrative text, b) questionnaire and c) interview to provide information about the process and the students' responses towards the use of story grammar strategy in teaching reading narrative text. The results of the study show that: 1) the teacher in general was successful in applying the story grammar based on the procedure of teaching instruction suggested by Florida Center for Reading Research (2007) and Gardill & Jitendra (1999). It can be seen from the development of the students' comprehension of narrative text in terms of identifying parts of story, reading comprehension test and retelling the story, 2) the students' responses towards the application of story grammar are positive because they thought that the program very helpful for them in comprehending narrative text. Based on the research findings, it is recommended that story grammar could be implemented in the teaching learning process and further research should involve a large number of students and teachers from different schools to gain more comprehensive result of the study.